Marine ecosystems : - Crowe,Tasman P. Frid,Christopher L J (Ecology, biodiversity and conservation, 2015)
Ecosystem services are emerging as a key driver of conservation policy and environmental management. Delivery of ecosystem services depends on the efficient functioning of ecosystems, which in turn depends on biodiversity and environmental conditions. Many marine ecosystems are extremely productive and highly valued, but they are increasingly threatened by human activities. With contributions from leading researchers, this volume synthesises current understanding of the effects on biodiversity and ecosystem functioning caused by a variety of human activities and pressures at play in coastal marine ecosystems. The authors examine the likely consequences for ecosystem service provision, covering key topics including fisheries, aquaculture, physical structures, nutrients, chemical contaminants, marine debris and invasive species. Critically reviewing the latest developments, this is a unique resource both for environmental managers and policy makers and for researchers and students in marine ecology and environmental management. -- Back cover. --